A Positive Mood Induction for Reducing the Formation of Nocebo Effects from Side Effect Information. Issue 11 (11th March 2019) - Geers, Andrew L; Close, Shane; Caplandies, Fawn C; Vase, Lene
Abstract: Background: Providing treatment side effect information can increase the occurrence of side effects through nocebo effects. Nocebo effects from side effect information raise a dilemma for health care, as there is an ethical obligation to disclose potential unpleasant treatment information to patients. Purpose: To test the hypothesis that a positive mood induction can block the development of nocebo effects that result from treatment side effect information. Methods: In a laboratory setting, healthy participants were assigned to one of four conditions in a between-subjects randomized factorial trial. First, participants took part in a mood induction procedure, with half receiving a positive mood induction and the other half a neutral mood induction. Next, participants were told they would experience transcranial direct current stimulation (tDCS). Prior to a sham tDCS task, half of the participants were informed that headache pain is a side effect of tDCS, whereas the other half were not given this information. Results: In the neutral mood condition, the provision of headache side effect information lead to a greater occurrence of headaches, more frequent headaches, and a higher maximum level of headache pain as compared to those given no side effect information. In the positive mood condition, a similar increase in headache pain did not manifest from the provision of side effect information. Conclusions: This is the first experiment to find that a positive mood induction can block the formation of nocebo effects that arise from side effect information. Inducing positive moods may be an effective strategy for reducing nocebo effects in a variety of clinical settings. Abstract : Instructions that a treatment would induce headache side effects increased headache reports in participants unless they were first experimentally induced into a positive mood state.